Adjectival Phrases in the Pamona Language Within a Narrow Scope - Tahir*, Moh.; ., Gazali; ., Idris; Wulandari Mosau, Anastasia (Riwayat: Educational Journal of History and Humanities, 2023)
his research aims to determine how adjectival phrases are used in the Pamona language within a small scope (family). The method used in this research is qualitative descriptive method with a focus on Adjectival Phrases in the Pamona Language within a Small Scope. The data collection techniques used are observation and literature review techniques, including (1) the author seeks and observes activities conducted through conversations, (2) the author distributes questionnaires, (3) understands and delves into the content of conversations and questionnaires, (4) studies and investigates things that occur in conversations, (5) records conversations and questionnaires containing Pamona adjectival phrases, (6) classifies or categorizes data, and (7) draws conclusions from the data. Based on the research conducted using Yosodiputro's theory, it can be concluded that there are three types of adjectival phrases in the Pamona language within a small scope, namely: (1) modikatif adjectival phrases, (2) coordinative adjectival phrases, and (3) apositive adjectival phrases